PENGARUH PERHATIAN ORANG TUA DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS XI PADA MATA PELAJARAN EKONOMI DI SMA HANG TUAH I SURABAYA - Nurul Zakiah Rosyada, (Pendidikan Ekonomi, 2011)
The study is aimed to analyze how parental attention and learning facilities influence the eleventh-graders learning outcomes in economics subject at Hang Tuah I Senior High School. The research used a quantitative approach of an associative type. The sample consisted of 118 out of 165 students. The data collection techniques used were documentation and questionnaires. The data were then analyzed by using multiple linier regression analysis. The result shows that the parental attention and learning facilities partially have significant effect on the learning outcomes because the presence of parental attention and adequate learning facilities will have an impact on the students learning outcomes. Furthermore, the parental attention and learning facilities simultaneously have significant influence on the learning outcomes.